The microscopic magnetisation of the superconductor PuCoGa5 - Hiess, A. (2007)
The intermetallic compound PuCoGa5 is a superconductor with a surprisingly high critical temperature of in which the superconductivity has been suggested to arise from magnetic fluctuations. We investigated the microscopic magnetic properties by polarised neutron diffraction on a single crystal of 242PuCoGa5. An induced moment is observed on both the Pu and the Co sites. The total magnetisation is significantly smaller than previously reported in agreement with recent magnetisation measurements. This result challenges the currently discussed models for the superconductivity in this weakly magnetic compound.